Voces: American historia, the untold history of Latinos [videorecording (DVD)] - Leguizamo, John (Mitu NGL, PBS Distribution, 2024)
Inspired by his quest to uncover Latino and Latina heroes and their contributions, Leguizamo takes viewers on a captivating journey, delving into both well-known and lesser-known stories of Latino history and contributions, spanning thousands of years from the Ancient Empires to the early 1970s. Through this exploration, he aims to shine a light on the rich and often overlooked history of Latinos while showcasing how Latino history is American history.